Infectious disease detection with private information - Saak, Alexander E. (International Food Policy Research Institute, 2012)
In this paper we study incentives to report clinically suspect situations in a simple model of an infectious animal disease with limited diagnostic resource. We characterize a transfer scheme that sustains credible reporting and implements an efficient test allocation. In a game without monetary transfers, credible reporting and first-best targeted testing are achievable in both laissez-faire and efficient disease control regimes when the disease occurrence among few well-informed producers is unlikely. When the number of producers is small, random testing is optimal under mandatory depopulation of untested animals, but credible reporting can be necessary for testing to improve welfare under laissez-faire disease control if private information is sufficiently precise. When the number of producers is large, random testing always improves welfare, and if private information is precise, disease occurrence is unlikely, and testing capacity is small, efficient testing is achievable without transfers in the efficient disease control regime.